Scabies Risk Factor Analysis in Students at Islamic Boarding School - Mawardi, Prasetyadi; Oktavriana , Triasari; Murasmita , Alamanda; Murastami , Ammarilis; Primisawitri , Pratiwi Prasetya; Rosyid , Azhar; Putri , Osdatilla Esa; Pradestine, Sesia (Faculty of Medicine, Universitas Airlangga, 2024)
Background: Scabies is a highly contagious skin disease that often occurs in densely populated settings, especially among children, including those in boarding schools. Purpose: We aimed to investigate the risk factors for scabies infestation in boarding schools. Methods: This crosssectional analytic research was conducted at the Imam Syuhodo Modern Islamic Boarding School. This study consisted of four main steps: survey questionnaires, a pre-test, one-on-one doctor examination, and a brief discussion. The collected data was analyzed using the ChiSquare test and bivariate analysis. Additional multivariate analysis was performed to determine the most influential risk factors. Result: The total sample for the study was 490 students (242 males and 248 females). The overall prevalence of scabies in the boarding school was 16.12%. Bivariate analysis showed a significant relationship between male sex, age (<14 years), history of itchiness, and sharing belongings. In the multivariate analysis, sex (OR 5.56, 95% CI 2.5911.93) and age (OR 2.09, 95% CI 1.23-3.56) turned out to be the most significant factor for scabies. Dermatology specific quality of life index assessment showed more severe negative effects on students with scabies (p<0.001). Discussion: Scabies prevalence was more common in younger males patients. The prevalence of male students was very disproportionate, which needs further attention when designing an intervention model. Students in boarding schools dealing with scabies have worse impacts on their daily lives, which could impede their academic progress.